The Subversive Potential of Laughter in Hinko Gottlieb’s Ključ od velikih vrata [The Key to the Great Gate] - Giergiel, Sabina (Poznańskie Studia Slawistyczne, 2023)
This paper focuses on a short work of fiction written in the 1940s by the Croatian Jew, Hinko Gottlieb. The manuscript of the book was found in one of the Jerusalem archives and,about seventy years later was, prepared for publication in Croatia in 2021. Undermining the readers’ previous habits, the book uncharacteristically problematises the Holocaust. Gottlieb uses humour as his major aesthetic device to describe internment. the story may also be ascribed to the fantasy genre, or to speculative fiction to be more precise. The purpose of the thought experiment presented here is to examine (in prison conditions) the possibilities that the socalled space capacitor has to offer. Besides acknowledging the occurrence in the text of such categories as science fiction, grotesque and surrealism, the article endeavours to answer the question about their use in the story of the Holocaust.